Determinants of Financial Management Behavior: Financial Literacy, E-wallet Use, and Lifestyle - Ika Rahma Aulia; Almira Santi Samasta; Diana Puspitasari; Suhita Whini Setyahuni (LP2M IAIN Palopo, 2026)
This study examines the influence of financial literacy, e-wallet usage, and lifestyle on financial management among undergraduate students of Management Program at Dian Nuswantoro University, based on the knowledge-behavior gap among Gen Z who actively use fintech but have low savings practices. The objective of the study is to analyze the causal relationship between these three variables using a quantitative explanatory approach with the PLS-SEM method. The population includes 1,617 active students in semesters 3-7 who have taken financial management courses and e-wallet users, with a sample of 178 respondents through purposive sampling. The instrument in the form of a Likert 1-5 questionnaire (15 indicators) was analyzed with SmartPLS 4 through validity tests (loading factor >0.7, AVE >0.5), reliability (CR >0.7), and bootstrapping hypothesis of 5000 subsamples. The results showed a significant positive influence on: financial literacy (β=0.377, p=0.000), lifestyle (β=0.286, p=0.006), e-wallet (β=0.204, p=0.010), with R²=0.584. The conclusion recommends the integration of e-wallet literacy into the curriculum to improve students' financial discipline.